Hubungan Fungsi Kognitif Dengan Kualitas Hidup Lansia - Yusmaida, Yusmaida; Zulkarnaini, Zulkarnaini (Yayasan Jompa Research and Development, 2024)
Indonesia ranks low (71st) in the Global Age Watch Index regarding elderly quality of life. This cross-sectional analytical study aimed to examine the relationship between cognitive function and quality of life among elderly individuals in Pusong Lama Village, Banda Sakti Subdistrict, Lhokseumawe City. The research involved the entire elderly population (n=62) using total sampling technique from July to October 2024. Data were collected using the Mini-Mental State Examination (MMSE) for cognitive function assessment and WHOQOL-BREF for quality of life evaluation, subsequently analyzed through chi-square statistical testing. Findings revealed that the majority of elderly participants exhibited mild cognitive impairment (48.4%) and moderate quality of life (40.3%). Statistical analysis demonstrated a significant correlation between cognitive function and quality of life (p=0.000 < 0.05), indicating that cognitive status significantly influences elderly life quality. These results underscore the critical importance of cognitive health interventions and knowledge enhancement to support comprehensive elderly care strategies and promote optimal aging.